Health and Structure of Morbidity College Students - Sergiу Savchuk; Volodymyr Kovalchuk (Lesya Ukrainka Volyn National University, 2015)
The article presents data on the prevalence of diseases among the students Lutsk National Technical University, based on a detailed medical review.